Silicon-carbon composite material, method for preparing the same, negative electrode, and energy storage device

CN122950461APending Publication Date: 2026-10-20LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611426341.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,对于氮气分子(动力学直径0.43nm)在77K下无法进入的闭孔结构,其作为孤立空腔对缓解硅膨胀的独特作用长期被忽视,这类闭孔形成的“死空间”可有效限制硅膨胀向颗粒外部的传递,却因缺乏标准化表征参数(如闭孔体积分数、闭孔分布均匀性)而难以量化评估

Benefits of technology

[0018]本发明具有以下有益效果:通过协同调控硅碳复合材料的高闭孔率与低骨架密度等结构参数,在材料颗粒内部构建大量孤立闭孔结构以有效缓冲体积膨胀效应。同时,得益于连续石墨化碳骨架的优异导电性和机械支撑作用,成功实现了高循环稳定性与高体积能量密度的协同优化。该高闭孔-低骨架密度复合结构可采用流化床化学气相沉积结合可控造孔/碳化工艺进行制备,其关键参数体系可通过氦气比重法、氮气吸附测试及原位透射电子显微镜等标准化表征手段进行无损检测。这种可量化、可重复的制备与表征方案,为产业界的规模化生产和质量管控提供了可靠的技术路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a silicon-carbon composite material, its preparation method, a negative electrode, and an energy storage device. The silicon-carbon composite material comprises a porous carbon framework and silicon filled within the porous carbon framework. The mass fraction of silicon in the silicon-carbon composite material is 20% to 85%, and nitrogen gas cannot enter a volume greater than 0.5 cm³. 3 / g, and the skeleton density of the silicon-carbon composite material, determined by the helium density method, is 0.6~1.2 g / cm³. 3 The porous carbon framework possesses a partially ordered graphitized structure. Its silicon-carbon composite material, through the synergy of a high nitrogen-inaccessible volume and low framework and compaction density, constructs numerous isolated closed-cell cavities within the composite material, providing ample buffer space for the volume expansion of silicon lithium intercalation. This allows the material to maintain low expansion and high cycling stability under wide silicon loads; simultaneously, the graphitized carbon framework provides a continuous conductive network and mechanical support.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to a silicon-carbon composite material, its preparation method, a negative electrode, and an energy storage device. Background Technology

[0002] As a high-efficiency energy storage device, the performance improvement of lithium-ion batteries is crucial for the development of new energy vehicles, consumer electronics, and energy storage systems. In the field of anode materials, silicon-based materials are considered an ideal choice for next-generation high-energy-density batteries due to their theoretical specific capacity far exceeding that of traditional graphite anodes. While elemental silicon boasts an extremely high theoretical capacity of 3579 mAh / g and a voltage of 0.4V (vs. Li-ion), it is still a significant challenge. + While Lithium has a low lithium intercalation potential, the approximately 300% volume expansion caused by the lithiation reaction during charging and discharging can damage the electrode structure, leading to problems such as active material stripping and repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, which severely restricts cycle life.

[0003] In current technologies, composite structures in which silicon nanoparticles are loaded onto porous carbon matrices via chemical vapor deposition have become the mainstream solution. The porous carbon framework provides a conductive network, and its pores act as buffer spaces to absorb volume changes in silicon. Existing research commonly uses nitrogen adsorption (BET) to characterize the open-pore structure of materials (pore size distribution, specific surface area, and open-pore volume) and optimizes material properties based on this. However, the unique role of closed-pore structures (where nitrogen molecules (kinetic diameter 0.43 nm) cannot enter at 77 K) in mitigating silicon expansion as isolated cavities has long been overlooked. These closed-pore "dead spaces" effectively limit the transfer of silicon expansion to the outside of the particles, but their quantitative evaluation is difficult due to the lack of standardized characterization parameters (such as closed-pore volume fraction and closed-pore distribution uniformity).

[0004] In industrial application, material design often faces a triple dilemma: 1) High silicon loads require more closed-cell buffers, but excessively high closed-cell ratios lead to low skeleton density measured by helium gravity, reducing volumetric energy density; 2) Electrode compaction density needs to balance conductivity (requiring high compaction) and expansion margin (requiring low compaction), but low-compacted electrodes lacking closed-cell support are prone to insufficient mechanical strength; 3) The degree of graphitization of the carbon skeleton affects conductivity, but this conflicts with the stability of the pore structure during the manufacturing process. Current technologies urgently require a porous silicon-carbon composite material that balances high cycle stability and high volumetric energy density under wide silicon loads.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a silicon-carbon composite material, a negative electrode, and an energy storage device to improve the above-mentioned technical problems.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a silicon-carbon composite material comprising a porous carbon skeleton and silicon filled in the porous carbon skeleton. The silicon mass fraction in the silicon-carbon composite material is 20% to 85%, and the nitrogen-inaccessible volume of the silicon-carbon composite material is greater than 0.5 cm³ / g. The skeleton density of the silicon-carbon composite material, determined by helium density measurement, is 0.6 to 1.2 g / cm³. The porous carbon skeleton has a graphitized structure, and the intensity ratio ID / IG of the D band to the G band in the Raman spectrum of the porous carbon skeleton is 0.60 to 0.95. The porous carbon skeleton has a graphite crystallite size La calculated according to Raman spectroscopy of 2 nm to 100 nm. The X-ray diffraction crystallinity of the porous carbon skeleton is 10% to 80%. The total pore volume of the porous carbon skeleton, determined by nitrogen adsorption, is 0.3 cm³ / g to 2.5 cm³ / g, and the proportion of micropores in its pore size distribution is >10%.

[0008] In an optional embodiment, the nitrogen-free volume of the silicon-carbon composite material is 0.6 cm³. 3 / g~1.0cm 3 / g; And / or, the average particle size of the silicon-carbon composite material is 2~15μm; And / or, the silicon mass fraction in the silicon-carbon composite material is 25% to 85%.

[0009] In an optional embodiment, the pore volume of micropores in its pore size distribution is >80%.

[0010] In an optional embodiment, the silicon-carbon composite material further comprises a carbonaceous surface layer that covers at least a portion of its surface.

[0011] In an optional embodiment, the carbonaceous surface layer accounts for 1% to 20% of the total mass of the silicon-carbon composite material. Preferably, the carbonaceous surface layer is formed by carbonization of a carbon-containing polymer.

[0012] Secondly, the present invention provides a method for preparing a silicon-carbon composite material as described in any of the foregoing embodiments, the preparation steps of which include: The porous carbon framework precursor is heated to the carbonization temperature for carbonization, and then activated to obtain a porous carbon framework. The activation temperature is 650~850℃ and the activation time is 1~3 hours. Then, silicon is deposited into the porous carbon framework through chemical vapor deposition at a temperature of 380℃~800℃ for 3~7 hours, so that the silicon phase fills the interior of the porous carbon framework, and then it is classified and sieved.

[0013] In an optional embodiment, the heating rate to the carbonization temperature is 1~5℃ / min, the carbonization temperature is 700~1500℃, and the carbonization time is 1~8 hours. And / or, the activator used in the activation treatment is KOH or H2O.

[0014] In an optional embodiment, during chemical vapor deposition, the silane volume fraction is controlled to be 10% to 90% and the system pressure is controlled to be 1 kPa to 100 kPa.

[0015] In an optional embodiment, when the silicon-carbon composite material includes a carbonaceous surface layer, before grading and sieving, it further includes mixing the silicon-deposited particles with a carbon-containing polymer and carbonizing them to form a carbonaceous surface layer that at least covers a portion of the particle surface.

[0016] Thirdly, the present invention also provides a negative electrode, which includes a current collector and an active material layer coated on the surface of the current collector, the active material layer including the silicon-carbon composite material as described in the foregoing embodiments.

[0017] Thirdly, the present invention provides an energy storage device, which includes a negative electrode as described in the foregoing embodiments, preferably a lithium-ion secondary battery.

[0018] This invention offers the following advantages: By synergistically controlling structural parameters such as high closed-pore ratio and low framework density in silicon-carbon composite materials, a large number of isolated closed-pore structures are constructed within the material particles to effectively buffer the volume expansion effect. Simultaneously, thanks to the excellent conductivity and mechanical support of the continuous graphitized carbon framework, synergistic optimization of high cycling stability and high volumetric energy density is successfully achieved. This high-closed-pore, low-framework-density composite structure can be prepared using fluidized bed chemical vapor deposition combined with a controllable pore-forming / carbonization process. Its key parameter system can be non-destructively tested using standardized characterization methods such as helium specific gravity method, nitrogen adsorption test, and in-situ transmission electron microscopy. This quantifiable and repeatable preparation and characterization scheme provides a reliable technical path for large-scale production and quality control in industry. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a schematic diagram of the microstructure of the silicon-carbon composite material in the negative electrode of the present invention. Figure 2This is a process flow diagram for preparing the silicon-carbon composite anode material of the present invention. Figure 3 This is a schematic diagram showing the relationship between the volume of sample inaccessible to nitrogen and the density of the skeleton (helium specific gravity method); Figure 4 This is a schematic diagram showing the relationship between the expansion of the sample's full-fill volume and the volume that nitrogen cannot enter.

[0021] Illustration: 001 - Carbonaceous surface layer; 002 - Porous carbon framework; 003 - Silicon; 004 - Closed pores. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0023] The definitions, testing, and calculation methods of the core performance parameters of this invention are as follows. All tests are conducted using industry-standard equipment and methods to ensure full disclosure and reproducibility:

[0024] The following is a detailed description of a silicon-carbon composite material, its preparation method, negative electrode, and energy storage device provided by the present invention.

[0025] Some embodiments of the present invention provide a silicon-carbon composite material, see [link to relevant documentation]. Figure 1 The silicon-carbon composite material comprises a porous carbon framework 002 and silicon 003 filled within the porous carbon framework 002. The mass fraction of silicon in the silicon-carbon composite material is 20% to 85%, and nitrogen gas cannot penetrate the silicon-carbon composite material in volumes greater than 0.5 cm³. 3 / g, meaning it has a large number of closed-cell 004, and the skeleton density of this silicon-carbon composite material, determined by helium density measurement, is 0.6~1.2 g / cm³. 3 Among them, the porous carbon framework 002 has a partially ordered graphitized structure.

[0026] By precisely controlling the microstructural parameters of silicon-carbon composite materials, synergistic optimization of performance was achieved. This involves the synergy of high closed-pore ratio and low framework density, constructing numerous isolated closed-pore cavities within the particles to buffer volume expansion, and utilizing the continuous conductivity and mechanical support of the graphitized carbon framework to achieve a balance between high cycling stability and high volumetric energy density.

[0027] Specifically, the mass fraction of silicon in silicon-carbon composite materials ranges from 20% to 85%. The silicon content directly determines the specific capacity of the material. For example, the mass fraction of silicon can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or any range between these values. If the silicon content is too low, the high capacity advantage of silicon cannot be realized; if the silicon content is too high, the proportion of the silicon phase is too large, the total expansion increases, and the low-density skeleton cannot support it, making the expansion problem difficult to control.

[0028] The nitrogen-inaccessible volume of the silicon-carbon composite material is greater than 0.5 cm³ / g. This nitrogen-inaccessible volume, also known as the closed-cell volume, reflects the total amount of pores within the composite particles that are isolated from each other and not connected to the outside environment. It acts as a "dead space" buffer for silicon lithium intercalation expansion. A higher value indicates a larger free volume within the particles available for expansion, which is the core parameter for achieving low expansion in this invention. For example, this value can be 0.51 cm³ / g, 0.55 cm³ / g, 0.6 cm³ / g, 0.65 cm³ / g, 0.7 cm³ / g, 0.75 cm³ / g, 0.8 cm³ / g, 0.85 cm³ / g, 0.9 cm³ / g, 0.95 cm³ / g, 1.0 cm³ / g, or higher. These closed pores, acting as built-in "buffer spaces," provide ample space to accommodate the volume expansion of silicon during lithium intercalation under a wide silicon load, effectively preventing overall particle expansion and cracking. When the nitrogen-inaccessible volume is no greater than 0.5 cm³ / g... 3 At / g, the closed-cell buffer space is insufficient, the expansion of silicon lithium intercalation lacks a place to accommodate it, the overall expansion rate of the particles increases dramatically, they are prone to cracking and pulverization during cycling, and the capacity decays rapidly.

[0029] Furthermore, the skeleton density of the silicon-carbon composite material, determined by helium density measurement, ranges from 0.6 to 1.2 g / cm³. For example, skeleton densities can be 0.6 g / cm³, 0.7 g / cm³, 0.8 g / cm³, 0.9 g / cm³, 1.1 g / cm³, and 1.2 g / cm³. The lower skeleton density corresponds to a higher closed-cell volume, together forming a lightweight skeleton structure with multiple buffer spaces. The partially graphitized structure provides the necessary electronic conductivity network and mechanical support for the composite material. This skeleton density parameter is greater than 0.5 g / cm³. 3 Nitrogen gas at a concentration of / g should not enter the volumetric synergy to ensure sufficient internal cavities in the particles without excessive densification; too high a concentration will result in insufficient pore closure and buffer failure, while too low a concentration will damage mechanical support and conductivity. This is especially important when the skeleton density is greater than 1.2g / cm³. 3 When the material exceeds the upward limit, it tends to become denser and the number of closed pores decreases. This is equivalent to nitrogen being unable to enter, resulting in a decrease in volume, a weakening of expansion buffer capacity, and deterioration of circulation and expansion.

[0030] Furthermore, to optimize performance, the present invention provides preferred limits to the above parameters. For example, the mass fraction of silicon in the silicon-carbon composite material is preferably 25% to 85%, such as 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, and more preferably 25% to 65%. The nitrogen-free volume of the silicon-carbon composite material is preferably 0.6 cm³ / g to 1.0 cm³ / g, such as 0.6 cm³ / g, 0.7 cm³ / g, 0.8 cm³ / g, 0.9 cm³ / g, and 1.0 cm³ / g.

[0031] The porous carbon framework 002 possesses a partially ordered graphitized structure. The degree of graphitization of the carbon framework is determined by Raman spectroscopy. I D / I G Characterization is performed using at least one of the following: graphite crystallite size (La), and X-ray diffraction crystallinity, reflecting the electronic conductivity and mechanical strength of the carbon framework. Specifically, for graphitized structures of porous carbon frameworks, they must satisfy at least one of the following characteristics: (a) Intensity ratio of D band to G band in the Raman spectrum of porous carbon framework 002 I D / I G The value ranges from 0.60 to 0.95, for example, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, and 0.95. This range indicates that the porous carbon framework 002 possesses both a certain degree of graphitization and the flexibility of amorphous carbon.

[0032] (b) The porous carbon framework 002 has a graphite crystallite size La calculated according to Raman spectroscopy of 2 nm to 100 nm, for example 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm.

[0033] (c) The X-ray diffraction crystallinity of the porous carbon framework 002 is 10% to 80%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, and 80%. These parameters collectively define the partially ordered graphitization state of the porous carbon framework 002, enabling it to provide good electrical conductivity while maintaining the structural flexibility required to form abundant closed pores.

[0034] It should be noted that excessive graphitization (excessive crystallinity) results in a rigid framework that is difficult to form closed pores; excessive amorphization ( I D / I GIf the window is too large, the conductivity will be poor. This window balances conductivity and aperture creation. When graphitization is severely insufficient (e.g. I D / I G When the value is greater than 0.95 (approaching amorphous carbon), the porous carbon framework 002 has poor electrical conductivity and hindered electron conduction, resulting in decreased rate and cycle performance.

[0035] The average particle size of silicon-carbon composite materials is 2~15μm, for example, 2μm, 3μm, 5μm, 7μm, 8μm, 10μm, 12μm, and 15μm. A suitable particle size helps shorten the lithium-ion diffusion path, improve rate performance, and ensure the uniformity of electrode coating. In some preferred embodiments, the average particle size is limited to 2~5μm, which can fully ensure dispersibility while avoiding excessively large particles that lead to excessively long ion diffusion paths, decreased fast-charging performance, and uneven electrode thickness. When the average particle size is greater than 5μm (e.g., reaching 8μm), the lithium-ion diffusion path is significantly lengthened, rate performance deteriorates, and large particles are prone to uneven distribution in the electrode, causing problems during rolling.

[0036] In some embodiments, to further optimize ion transport and silicon deposition uniformity, the total pore volume of the porous carbon framework was determined to be 0.3 cm³ using nitrogen adsorption. 3 / g~2.5cm 3 / g, and the proportion of micropore volume in its pore size distribution is >10%, preferably >80%.

[0037] In some implementations, see again Figure 1 The silicon-carbon composite material also includes a carbonaceous surface layer 001 covering at least a portion of its surface. This carbonaceous surface layer can further stabilize the electrode / electrolyte interface and improve the initial coulombic efficiency. The carbonaceous surface layer accounts for 1% to 20% of the total mass of the silicon-carbon composite material, for example, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, and 20%. Preferably, the carbonaceous surface layer is carbonized from a carbon-containing polymer (such as pitch, phenolic resin, polyvinyl alcohol, etc.). This carbon layer is dense and uniform, effectively isolating the active silicon from direct contact with the electrolyte. It should be noted that when the carbonaceous surface layer accounts for more than 20% (beyond the limit), the mass of inactive carbon is excessive, diluting the active silicon, reducing the specific capacity, and the initial coulombic efficiency decreases due to additional surface side reactions.

[0038] Further, see Appendix Figure 2 Some embodiments of the present invention also provide a method for preparing the above-mentioned silicon-carbon composite material, which includes the following steps: S1. Preparation of porous carbon framework: Using one or more of pitch-based, resin-based, biomass-based, or metal-organic framework-derived carbon as raw materials, and through activation pore formation and controllable graphitization heat treatment, a graphitized structure is obtained. ID / I G 0.60~0.95, La 5~100 nm, XRD crystallinity 10%~80%, skeletal density 0.6~1.2 g / cm³ 3 (Helium specific gravity method) and rich in closed-pore porous carbon framework; the formation of closed pores can be controlled by the degree of activation and the heat treatment temperature curve. The degree of activation refers to the pre-formation of an appropriate amount of open pores at low temperature by precisely controlling the activation temperature (e.g., 700℃) and the amount of pore-forming agent (e.g., 10wt%), providing a structural basis for the subsequent high-temperature closed-pore transformation. The temperature curve refers to the use of a relatively slow heating rate (1-5℃ / min) and precise setting of the carbonization peak temperature (e.g., 1300-1500℃) to guide the orderly rearrangement of the carbon layer at high temperature, driving the closure of the open pore edges and transforming them into closed pores.

[0039] S2. Fluidized Bed Chemical Vapor Deposition of Silicon: A porous carbon framework is placed in a fluidized bed reactor, and a mixture of silicon precursor (one or more of silane, dichlorosilane, trichlorosilane or silicon tetrachloride) and inert carrier gas or hydrogen is introduced. At a deposition temperature of 350℃ to 800℃, by controlling the silane volume fraction (e.g., 10% to 90%), system pressure (1 kPa to 100 kPa) and deposition time, the silicon phase is filled into the porous carbon framework (including closed pores and open pores), and finally the silicon mass fraction reaches 20% to 85%.

[0040] S3. Construction of a carbonaceous surface layer: The silicon-deposited particles are mixed with carbon-containing polymers (such as asphalt, phenolic resin, polyvinyl alcohol, etc.) and carbonized to form a carbonaceous surface layer that at least partially covers the particle surface, accounting for 1% to 20% of the total mass. Nitrogen gas must not enter the volume greater than 0.5 cm³. 3 / g.

[0041] S4. Grading and characterization: The average particle size was controlled by sieving, and the framework density, nitrogen-inaccessible volume, pore size distribution and lithiation expansion rate were confirmed to fall within the specified range by helium gravity method, nitrogen adsorption method and in-situ transmission electron microscopy.

[0042] The negative electrode preparation process provided by some embodiments of the present invention involves mixing the above-mentioned silicon-carbon composite material, conductive agent (such as carbon black, carbon nanotubes) and binder (such as polyvinylidene fluoride, styrene-butadiene rubber) to form a slurry, coating it onto a current collector (such as copper foil), and then drying and rolling it.

[0043] Some embodiments of the present invention further provide an energy storage device including the aforementioned negative electrode. Preferably, the energy storage device is a lithium-ion secondary battery, which further includes a positive electrode, a separator, and an electrolyte. Due to the use of the silicon-carbon composite material of the above embodiments of the present invention, this lithium-ion secondary battery exhibits high energy density, excellent fast charge / discharge capability, and long cycle life.

[0044] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0045] It should be noted that the testing conditions for all samples were consistent: framework density was measured using the helium specific gravity method; total pore volume, pore size distribution, and accessible pore volume were measured using nitrogen adsorption at 77 K, and the results were analyzed according to V... N2 =1 / ρ sk 1 / ρ0 V open Calculate the volume inaccessible to nitrogen; determine the silicon mass fraction using air TGA; characterize the graphitization structure using Raman / XRD; measure the lithiation expansion rate using in-situ transmission electron microscopy; measure the first-cycle coulombic efficiency and 0.1C reversible specific capacity of a half-button cell; characterize the cycle life by measuring the capacity retention rate after 500 cycles of 4C charge / 1C discharge; improve the volumetric energy density of the cell by comparing it with a conventional silicon-carbon benchmark cell of equivalent design.

[0046] Semi-button battery assembly: Assemble CR2032 button batteries in a glove box, using lithium metal sheets as the counter electrode, polypropylene microporous membranes as the separator, and LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC=1:1), with a LiPF6 concentration of 1 mol / L.

[0047] (1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, conductive agent SuperP, binder PVDF and solvent NMP are mixed evenly in a mass ratio of 92:3:5:150 and then evenly coated on the positive electrode current collector. Then, it is dried at 80℃ to obtain the positive electrode sheet.

[0048] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent SP, binder PAA, thickener CMC, binder SBR and solvent deionized water are mixed evenly in a mass ratio of 95:1:2:1:1:120 and then evenly coated on the negative electrode current collector. After drying at 80°C, the negative electrode sheet is obtained by roller pressing.

[0049] (3) The positive and negative electrode sheets are stacked in a square and separated by a polypropylene separator to form a battery cell, which is then packaged into an aluminum-plastic bag. An electrolyte of the appropriate capacity is injected into the aluminum-plastic bag, and the bag is vacuum sealed to obtain a soft-pack battery. The electrolyte is a mixture of LiPF6 EC and DEC, wherein the concentration of LiPF6 is 1 mol / L and the volume ratio of EC to DEC is 1:1.

[0050] Example 1 Step (1), Preparation of asphalt-based porous carbon: The asphalt raw material is pre-oxidized at 300℃ in an O2 atmosphere, and then heated to 800℃ and held at that temperature for 2 hours in an inert atmosphere to obtain asphalt-based carbon material; The asphalt-based carbon material is mixed with an activator in a certain proportion and activated at 750℃ for 1.5 hours in an inert atmosphere to obtain an activated product; The activated product is then subjected to acid washing, water washing and drying to obtain the asphalt-based porous carbon; The activator is KOH, the mass ratio of asphalt-based carbon material to activator is 1:2, and the rate of heating to the carbonization temperature is 5℃ / min.

[0051] The resulting pitch-based porous carbon graphitized structure I D / I G =0.80, La=20 nm, XRD graphitization 30%, total pore volume of nitrogen adsorption 0.55 cm⁻¹ 3 / g (55% micropores, 45% mesopores).

[0052] Step (2): Place the above porous carbon in a fluidized bed and heat it to 550°C in an argon atmosphere; switch to SiH4 gas (60% by volume) carried by argon and deposit it for 5 hours at a system pressure of 8 kPa; stop SiH4 and cool it to room temperature in argon to obtain silicon-carbon material.

[0053] Step (3): Place the above product in a rotary kiln and heat it to 500-800°C under an inert atmosphere (argon). Then, introduce a mixture of carbon source gas (methane) and carrier gas with a carbon source gas volume fraction of 15%. Deposit at a constant temperature for 2 hours to allow the carbon source to decompose and deposit on the particle surface to form a carbon coating layer. After deposition, cool to room temperature under an inert atmosphere to obtain the carbon-coated silicon-carbon composite material. The carbon source gas flow rate is 100-500 sccm, and the carrier gas is argon with a flow rate of 500-2000 sccm.

[0054] The resulting material has a silicon mass fraction of 35%, an average particle size of 7.6 μm, a carbonaceous surface layer content of 2%, and a framework density of 1.04 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.01 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.506cm³. 3 / g.

[0055] Performance: First-cycle coulomb efficiency 81.2%, 0.8V reversible specific capacity 1160 mAh / g, 500 cycles capacity retention rate of 4C charge / 1C discharge 90.1%, and full charge volume expansion 32%.

[0056] Example 2 This embodiment uses the same preparation method as Example 1, except that it employs resin-based porous carbon. The preparation method of the resin-based porous carbon includes the following steps: curing a resin precursor, then heating it to the carbonization temperature under an inert atmosphere to obtain a carbonized product; activating the carbonized product using a physical activation method to obtain an activated product; and sequentially acid-washing, water-washing, and drying the activated product to obtain the resin-based porous carbon. The resin precursor is selected from phenolic resin or ion exchange resin; the physical activation method uses H2O as the activator, activates it at 800°C for 4.5 hours, and the water inlet flow rate is 2 ml / min; the rate of heating to the carbonization temperature is 5°C / min, the carbonization temperature is 600°C, and the carbonization time is 6 hours.

[0057] Resin-based porous carbon: graphitized structure I D / I G =0.75, La=15 nm, XRD graphitization degree 25%, total pore volume 0.45 cm³ 3 / g (65% micropores, 35% mesopores); fluidized bed CVD deposition of silicon (60% silane volume fraction, 8 kPa system pressure, 430℃ deposition for 4.5 h).

[0058] The resulting material has a silicon mass fraction of 30%, an average particle size of 8.0 μm, a carbonaceous surface layer content of 1.8%, and a framework density of 1.01 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.005 cm³. 3 / g, calculations show that the volume of nitrogen that cannot enter is 0.538cm³. 3 / g.

[0059] Performance: First-cycle coulomb efficiency 80.9%, 0.8V reversible specific capacity 901 mAh / g, 500 cycles of 4C charge / 1C discharge capacity retention 89.3%, full charge volume expansion 28%.

[0060] Example 3 The preparation method in this embodiment is the same as that in Example 1, except that a metal-organic framework (MOF) is used to derive a porous carbon framework. The preparation method of the MOF-derived porous carbon is as follows: the MOF precursor is placed in an inert atmosphere and heated to the carbonization temperature for high-temperature pyrolysis to obtain a carbonized product; the carbonized product is then acid-washed to remove metal species, washed with water until neutral, and dried to obtain the MOF-derived porous carbon; wherein the MOF precursor is selected from at least one of ZIF-8, ZIF-67, MOF-5, or bimetallic MOF; the carbonization temperature is 1000℃, the heating rate is 5℃ / min, the holding time is 6 hours, and the activation treatment is the same as in Example 1.

[0061] Porous carbon graphitized structure I D / I G =0.85, La=25 nm, XRD graphitization 35%, total pore volume 0.40 cm³ 3 / g (77% micropores, 23% mesopores); fluidized bed CVD deposition of silicon (60% silane volume fraction, 12 kPa system pressure, 470℃ deposition for 3.8 h).

[0062] The resulting material has a silicon mass fraction of 25%, an average particle size of 6.9 μm, a carbonaceous surface layer content of 1.1%, and a framework density of 0.9 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.008 cm³. 3 / g, calculations show that the volume of nitrogen that cannot enter is 0.655cm³. 3 / g.

[0063] Performance: First-cycle coulomb efficiency 81.7%, 0.8V reversible specific capacity 820mAh / g, 500-cycle capacity retention rate of 4C charge / 1C discharge 90.6%, and volume expansion of 21% when fully charged.

[0064] Comparative Example 1 This comparative example uses the same porous carbon framework and silicon loading as Example 1. The asphalt raw material is pre-oxidized at 300°C in an O2 atmosphere, then heated to 500°C and held for 3 hours in an inert atmosphere, followed by carbonization at 800°C and held for 2 hours to obtain asphalt-based carbon material. The asphalt-based carbon material is mixed with an activator in a certain proportion and activated at 750°C for 1.5 hours in an inert atmosphere, followed by activation at 950°C for 2 hours to obtain an activated product. The activated product is then subjected to acid washing, water washing, and drying to obtain the asphalt-based porous carbon. The activator is KOH, the mass ratio of the asphalt-based carbon material to the activator is 1:3.5, and the rate of heating to the carbonization temperature is 2°C / min. Gradient carbonization and activation reduce the number of closed pores. The resulting material has a silicon mass fraction of 35%, an average particle size of 7.6 μm, a carbonaceous surface layer ratio of 2.0%, and a framework density of 1.8 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.008 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.102cm³. 3 / g.

[0065] Performance: First-cycle coulombic efficiency 80.5%, 0.8V reversible specific capacity 1175mAh / g, 500 cycles of 4C charge / 1C discharge capacity retention 82.2%, full-charge volume expansion 66%. Insufficient closed-pore buffering leads to uncontrolled expansion and cycle degradation.

[0066] Comparative Example 2 This comparative example uses the same structure as Example 1, except that the SiH4 gas deposition time in step (2) is 6.5 hours, which increases the framework density to 2.0 g / cm³. 3 The resulting material had a silicon mass fraction of 45%, an average particle size of 7.3 μm, a carbonaceous surface layer content of 1.3%, and a framework density of 1.93 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.003 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.054cm³. 3 / g.

[0067] Performance: First-cycle coulombic efficiency 81.9%, 0.8V reversible specific capacity 1495mAh / g, 500 cycles of 4C charge / 1C discharge capacity retention 78.1%, full charge volume expansion 59%. Excessive silicon deposition resulted in excessively high skeleton density.

[0068] Comparative Example 3 The only difference between this comparative example and Example 1 is that ungraphitized resin-based porous carbon with a graphitization degree of only 5% was used. A gradient activation process was employed to reduce the number of closed pores, resulting in a silicon mass fraction of 37.1%, an average particle size of 7.8 μm, a carbonaceous surface layer ratio of 1.2%, and a framework density of 1.9 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.006 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.075cm³. 3 / g.

[0069] Performance: First-cycle coulombic efficiency 80.0%, 0.8V reversible specific capacity 1380mAh / g, 500-cycle capacity retention of 81.5% (4C charge / 1C discharge), and 71% volume expansion at full charge. Insufficient closed-pore buffering leads to uncontrolled expansion and cycle degradation; at the same time, the initial efficiency is low, and cycle retention is poor.

[0070] The parameters and performance data of silicon-carbon composite materials are summarized in Table 1.

[0071] Table 1

[0072] In summary, the negative electrode provided by this invention, whose active material is a silicon-carbon composite material, achieves the following beneficial effects through the synergistic structure of "high closed-cell buffer + low framework density + graphitized conductive framework": Excellent cycling performance and controlled expansion: By constructing a nitrogen-free volume (closed pores) with a density greater than 0.5 cm³ / g, sufficient internal buffer space is provided for the volume expansion of silicon, keeping the overall expansion rate of the particles at a low level and significantly improving the cycling stability of the electrode.

[0073] Balancing volumetric energy density: The design of low skeleton density and low compaction density ensures the internal buffer cavity while avoiding excessive material densification, thus improving the volumetric energy density of the cell while maintaining high capacity.

[0074] Excellent electrical conductivity and mechanical support: The partially ordered graphitized carbon skeleton provides a continuous electronic conduction channel and a stable mechanical skeleton, effectively mitigating the increase in electrode impedance and structural collapse caused by repeated expansion and contraction of silicon.

[0075] High process adaptability: The material structure of this invention can be prepared by a mature fluidized bed chemical vapor deposition combined with a controllable pore-forming / carbonization process. All key parameters can be non-destructively characterized by conventional methods such as helium specific gravity measurement, nitrogen adsorption method, Raman spectroscopy, and in-situ transmission electron microscopy, which facilitates industrial production and quality control.

[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A silicon-carbon composite material, characterized in that, The silicon-carbon composite material comprises a porous carbon framework and silicon filling the porous carbon framework. The silicon mass fraction in the silicon-carbon composite material is 20% to 85%, and nitrogen gas cannot enter the silicon-carbon composite material in volumes greater than 0.5 cm³. 3 / g, and the skeleton density of the silicon-carbon composite material, determined by the helium density method, is 0.6~1.2 g / cm³. 3 The porous carbon framework has a graphitized structure, and the intensity ratio of the D band to the G band in the Raman spectrum of the porous carbon framework is... I D / I G The porous carbon framework has a graphite crystallite size La of 2 nm to 100 nm calculated according to Raman spectroscopy, with an X-ray diffraction crystallinity of 10% to 80%, and a total pore volume of 0.3 cm³ as determined by nitrogen adsorption. The crystallinity is 0.60–0.

95. 3 / g~2.5cm 3 / g, and the proportion of micropore volume in its pore size distribution is >10%.

2. The silicon-carbon composite material according to claim 1, characterized in that, The nitrogen-free volume of the silicon-carbon composite material is 0.6 cm³. 3 / g~1.0cm 3 / g; And / or, the average particle size of the silicon-carbon composite material is 2~15μm; And / or, the silicon is introduced and prepared by a chemical vapor deposition process, wherein the deposition temperature of the chemical vapor deposition is 380℃~800℃.

3. The silicon-carbon composite material according to claim 1 or 2, characterized in that, The silicon-carbon composite material also includes a carbonaceous surface layer that covers at least a portion of its surface.

4. The silicon-carbon composite material according to claim 3, characterized in that, The carbonaceous surface layer accounts for 1% to 20% of the total mass of the silicon-carbon composite material, and the carbonaceous surface layer is formed by carbonization of a carbon-containing polymer.

5. A method for preparing a silicon-carbon composite material as described in any one of claims 1 to 4, characterized in that, Its preparation steps include: The porous carbon framework precursor is heated to the carbonization temperature for carbonization, and then activated to obtain a porous carbon framework. The activation temperature is 650~850℃ and the activation time is 1~3 hours. Then, silicon is deposited into the porous carbon framework through chemical vapor deposition at a temperature of 380℃~800℃ for 3~7 hours, so that the silicon phase fills the interior of the porous carbon framework, and then it is classified and sieved.

6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that, The heating rate to the carbonization temperature is 1~5℃ / min, the carbonization temperature is 700~1500℃, and the carbonization time is 1~8 hours; And / or, the activator used in the activation treatment is KOH or H2O.

7. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that, During chemical vapor deposition, the volume fraction of silane is controlled to be 10%~90% and the system pressure is 1kPa~100kPa.

8. The method for preparing the silicon-carbon composite material according to claim 7, characterized in that, When the silicon-carbon composite material includes a carbonaceous surface layer, before grading and sieving, it further includes mixing the silicon-deposited particles with a carbon-containing polymer and carbonizing them to form a carbonaceous surface layer that at least covers a portion of the particle surface.

9. A negative electrode, characterized in that, It includes a current collector and an active material layer coated on the surface of the current collector, the active material layer including the silicon-carbon composite material as described in any one of claims 1 to 4.

10. An energy storage device, characterized in that, It includes the negative electrode as described in claim 9, and the energy storage device is a lithium-ion secondary battery.